2012
DOI: 10.1021/nn301096n
|View full text |Cite
|
Sign up to set email alerts
|

Induced Coiling Action: Exploring the Intrinsic Defects in Five-Fold Twinned Silver Nanowires

Abstract: Growth of polythiophene (PTh) on five-fold twinned Ag nanowires (NWs) is not symmetrical due to preferred etching of their intrinsic defects. This imbalance of polymer formation leads to consistent bending action along the etched NWs, coiling the resulting Ag-PTh nanocomposites into planar spirals. We studied the etching intermediates and also the effects of the surface ligands in order to understand the symmetry-breaking action. The defect-dependent etching chemistry offers a new means to induce motion and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…However, to the best of our knowledge, no room‐temperature graphene/semiconductor NW heterojunction near‐infrared photodetectors have been reported. With unique one‐dimensional (1D) structural characteristics and versatile physical properties, semiconductor NWs have received considerable attention as potential building blocks for various fundamental optical and electronic devices or systems . In particularly, InAs NW is a promising candidate material for near‐infrared detection due to its narrow band‐gap for infrared detection, high carrier mobility, large surface‐to‐volume ratio, ease of Ohmic contacts, and high photoresponsivity .…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, no room‐temperature graphene/semiconductor NW heterojunction near‐infrared photodetectors have been reported. With unique one‐dimensional (1D) structural characteristics and versatile physical properties, semiconductor NWs have received considerable attention as potential building blocks for various fundamental optical and electronic devices or systems . In particularly, InAs NW is a promising candidate material for near‐infrared detection due to its narrow band‐gap for infrared detection, high carrier mobility, large surface‐to‐volume ratio, ease of Ohmic contacts, and high photoresponsivity .…”
Section: Introductionmentioning
confidence: 99%
“…25 Recently, Chen′s group focused on this topic and proposed several innovative and reliable mechanisms, and most of these reports are related to polymer induction. [26][27][28][29][30] Chen et al have shown that bundles of carbon nanotubes 27 or gold nanowires 28 can be coiled into ring structures by controlling the contractions of their polymer shells. Then they further demonstrated that other factors, such as intrinsic defect induction 29 or the zipper mechanism, 30 were also key points to induce the polymerstabilized gold nanowires to coil into ring structures.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] Chen et al have shown that bundles of carbon nanotubes 27 or gold nanowires 28 can be coiled into ring structures by controlling the contractions of their polymer shells. Then they further demonstrated that other factors, such as intrinsic defect induction 29 or the zipper mechanism, 30 were also key points to induce the polymerstabilized gold nanowires to coil into ring structures. Although the above methods can be used to fabricate nanorings, the major disadvantage is the complicated process due to the complex molecular structures of the polymers and the multiple steps.…”
Section: Introductionmentioning
confidence: 99%
“…Their spiral growths were mainly induced by electrostatic interaction between opposite charged neighboring surfaces or by dislocation existing in crystals. Last but not least, coiled nanostructures can also be prepared in liquid circumstances and the mechanisms are usually involved with bending nanowires in confined micro-environments, or minimizing of the surface energy of nanowires 24 25 26 27 28 . Besides inorganic spiral nanostructures, organic materials of spiral nanostructures were also synthesized, mainly based on molecular self-assembly 29 30 .…”
mentioning
confidence: 99%